DESAIN TAPAK DAN STRATEGI PENGEMBANGAN ODTW DANAU UNGU DI KELURAHAN CEMPAKA - Rahmat Hidayat; Abdi Fithria; Fonny Rianawati (Jurnal Sylva Scienteae, 2022)
This research aims to identify the potential and tourist attractions in Cempaka Village by examining the preferences and perceptions of the parties towards tourism development as well as compiling recommendations for tourism development strategies and making site designs for tourist attractions in Cempaka Village. This research conducted was research in Cempaka Village, Cempaka Subdistrict, Banjarbaru City, South Kalimantan for 3 months. Analyze data utilizing SWOT. The outcomes showed that travel industry in Cempaka Town is Lake Ungu, the advancement methodology for Lake Ungu from the aftereffects of the investigation of interior and esternal variables of Lake Ungu, specifically 1.95 and 1.75 which are in quadrant II this position shows solid. be that as it may, faces incredible difficulties. The Telaga Ungu site configuration utilizes the idea of the travel industry which gives an assortment of visits in a single traveler area.Penelitaian ini bertujuan untuk mengidentifikasi potensi dan daya tarik wisata di Kelurahan Cempaka dengan mengkaji preferensi dan persepsi para pihak terhadap pengembangan wisata serta menyusun rekomendasi strategi pengembangan wisata dan membuat desain tapak objek daya tarik wisata di Kelurahan Cempaka. Penelitian ini dilakukan di Kota Cempaka, Wilayah Cempaka, Kota Banjarbaru, Kalimantan Selatan Selam 3 bulan. Analisis data menggunakan SWOT. Hasil penelitian menujukan wisata yang terdapat di Kelurahan Cempaka yaitu Danau Ungu, Strategi pengembangan untuk Danau Ungu dari hasil analisis faktor internal dan eksternal Danau Ungu yaitu 1,95 dan 1,75 yang Berada di kuadran II posisi ini menunjukkan solid namun menghadapi kesulitan besar. Desain tapak Danau Ungu menggunakan konsep wisata yang memberikan beragam wisata di dalam satu lokasi wisata